Analisis Yuridis Peningkatan Pelayanan Paspor Di Era Digital Pada Kantor Imigrasi Kelas II Belawan Ditinjau Menurut UU No 6 Tahun 2011 - Andreas Virga Siahaan; Tri Reni Novita (Albayan Journal of Islam and Muslim Societies, 2024)
This research aims to analyse the improvement of passport services in the digital era at the Class II Belawan Immigration Office from a juridical point of view, specifically based on Law Number 6 of 2011 concerning Immigration. The main focus of this research includes three aspects, namely: legal arrangements related to passport services according to laws and regulations, identification of obstacles in the implementation of digital services, and solutions applied by the Immigration Office in overcoming these problems.The research method used is empirical juridical method, with data collection techniques through literature study and direct interviews with immigration officers and academics in the field of state administrative law. The results showed that digital passport services have had a positive impact on the efficiency and transparency of public services. However, there are still obstacles in the form of a lack of public digital literacy, technological infrastructure constraints, and the need to strengthen personal data protection.In conclusion, the digitalisation of passport services is a policy that is legally valid and in accordance with immigration principles. To create inclusive and sustainable services, synergy between the government, the community, and the private sector is needed in terms of education, system strengthening, and legal protection.